O CONHECIMENTO PEDAGÓGICO DOS DOCENTES DE QUÍMICA DO ENSINO SUPERIOR - Cátia S. F. Primon; Agnaldo Arroio (Química Nova, 2016)
This study aims to investigate the pedagogical knowledge of Higher Education Chemistry teachers. From the perspective of qualitative research, questionnaires were given, there was documentary analysis and were interviewed twenty-six teachers of the Institute of Chemistry of an institution of state public higher education of São Paulo. Discussed the relevance of pedagogic disciplines in Postgraduate courses and participation in monitoring programs and teacher training in higher education teacher formation. It was found that most teachers lack pedagogical training and some do not show interest in the subject, but look for ways to overcome the difficulties encountered. The results obtained demonstrate the urgency to rethink and reorganize the PostGraduate courses before the real need for training of teachers for higher education.